The Relationship Between Teaching Methods and Human Resources and the Quality of Education at Ashabul Qur’an (Aqur) School in Payakumbuh - Ahmad Rifki; Hamdi Abdul Karim (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The quality of education at Al-Qur’an-based educational institutions is influenced by various factors, including teaching methods and the quality of human resources; therefore, efforts are needed to identify the relationship between these two factors in supporting the improvement of educational quality. This study aims to analyze the relationship between teaching methods and human resources—both partially and simultaneously—on the quality of education at the Ashabul Qur’an (AQUR) School in Payakumbuh. The study employed a quantitative approach using a correlational method. All 52 active teachers were selected as the sample through total sampling. Data were collected using a questionnaire that met validity and reliability requirements, then analyzed using descriptive statistics, normality tests, linearity tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that teaching methods are positively and significantly correlated with educational quality (β = 0.583; p = 0.005), as are human resources (β = 0.727; p = 0.002). Simultaneously, both variables are positively and significantly associated with the quality of education (F = 22.388; p < 0.001) with a coefficient of determination of 47.7%. These findings indicate that improving the quality of education requires strengthening teachers’ competencies as well as implementing effective teaching methods as key strategies for enhancing the quality of the learning process and outcomes in Qur’an-based educational institutions.